Konseptualisasi Green Marketing:Pendekatan Pemasaran Dalam Upaya Mempertahankan Loyalitas Pada Klinik Navaagreen Tiban Kota Batam - Triana Ananda Rustam; Inda Sukati (LPPM Universitas Putera Batam, 2023)
This research aims to examine the emergence of the back to nature movement which influences the lifestyle of millennial people who prefer environmentally friendly products in skincare products that are based on green products even though they are more expensive. Products that still use containers or raw materials that are not environmentally friendly are no longer a top priority. The next phenomenon is the increasing awareness of having healthy skin, which is a unique form of consumer behavior, especially experienced by women. The increasing trend in beauty care has also encouraged the growth of beauty products that do not have official permission from the Food and Drug Supervisory Agency (BPOM). Indirectly, this will reduce the level of consumer use of beauty products in the long term. This research contextually includes four supporting dimensions which provide the foundation for the existence of green marketing-based skincare products, namely green product, green price, green place and green promotion. This research uses a quantitative survey method with samples taken from 100 users of Naavagreen beauty clinic services. This research is a quantitative descriptive research where the data analysis process uses linear regression analysis between construct variables. The results of the research are that variables X1, X2 and X3 have a positive and significant effect, while variable X4 has a negative and insignificant effect. Meanwhile, simultaneously the variables in this research have a positive and significant effect.